Biomimetic Scaffolds for Spinal Cord Applications Exhibit Stiffness‐Dependent Immunomodulatory and Neurotrophic Characteristics. Issue 3 (25th November 2021) - Woods, Ian; O'Connor, Cian; Frugoli, Lisa; Kerr, Seán; Gutierrez Gonzalez, Javier; Stasiewicz, Martyna; McGuire, Tara; Cavanagh, Brenton; Hibbitts, Alan; Dervan, Adrian; O'Brien, Fergal J.
Abstract: After spinal cord injury (SCI), tissue engineering scaffolds offer a potential bridge for regeneration across the lesion and support repair through proregenerative signaling. Ideal biomaterial scaffolds that mimic the physicochemical properties of native tissue have the potential to provide innate trophic signaling while also minimizing damaging inflammation. To address this challenge, taking cues from the spinal cord's structure, the proregenerative signaling capabilities of native cord components are compared in vitro. A synergistic mix of collagen‐IV and fibronectin (Coll‐IV/Fn) is found to optimally enhance axonal extension from neuronal cell lines (SHSY‐5Y and NSC‐34) and induce morphological features typical of quiescent astrocytes. This optimal composition is incorporated into hyaluronic acid scaffolds with aligned pore architectures but varying stiffnesses (0.8–3 kPa). Scaffolds with biomimetic mechanical properties (<1 kPa), functionalized with Coll‐IV/Fn, not only modulate primary astrocyte behavior but also stimulate the production of anti‐inflammatory cytokine IL‐10 in a stiffness‐dependent manner. Seeded SHSY‐5Y neurons generate distributed neuronal networks, while softer biomimetic scaffolds promote axonal outgrowth in an ex vivo model of axonal regrowth. These results indicate that the interaction of stiffness and biomaterial composition plays an essential role in vitro in generating repair‐critical cellular responses and demonstrates the potential of biomimetic scaffold design. Abstract : Stiffness and composition play important roles in directing the response of cells to the implanted material. This study demonstrates that scaffolds containing a synergistic mix of spinal cord‐native proteins and biomimetic mechanical properties can direct astrocytes to adopt phenotypes associated with the repair while enhancing axonal growth in a stiffness‐dependent manner.